2009
DOI: 10.2461/wbp.2009.5.13
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Response of Sympatric Deer to Fire Using Stable Isotope Analysis of Liver Tissue

Abstract: Carbon (δ 13 C) and nitrogen (δ 15 N) isotopes in biological samples from large herbivores identify photosynthetic pathways (C 3 vs. C 4) of plants they consumed and can elucidate potential nutritional characteristics of dietary selection. Because large herbivores consume a diversity of forage types, δ 13 C and δ 15 N in their tissue can index ingested and assimilated diets through time. We assessed δ 13 C and δ 15 N in metabolically active liver tissue of sympatric mule deer (Odocoileus hemionus) and white-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Habitats, diets, behavior, and physiology of sympatric mule and white-tailed deer have been compared using a wide variety of techniques, such as direct behavioral observations (Lingle 2001(Lingle , 2002, stable isotope analysis (Walter et al 2009), microhistological analysis (Whitney et al 2011), review papers (Hygnstrom et al 2008), VHF and GPS radio-collars (Smith 1987, Robinson et al 2002, Avey et al 2003, Brunjes et al 2006, Dellinger et al 2018, and common garden experiments with tractable animals (Berry et al 2019, Hull et al 2020. However, ours is the first to use camera traps to study the effects of both fine and larger-scale habitat characteristics and potential displacement by a conspecific on the occupancy of mule and white-tailed deer in an area of sympatry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitats, diets, behavior, and physiology of sympatric mule and white-tailed deer have been compared using a wide variety of techniques, such as direct behavioral observations (Lingle 2001(Lingle , 2002, stable isotope analysis (Walter et al 2009), microhistological analysis (Whitney et al 2011), review papers (Hygnstrom et al 2008), VHF and GPS radio-collars (Smith 1987, Robinson et al 2002, Avey et al 2003, Brunjes et al 2006, Dellinger et al 2018, and common garden experiments with tractable animals (Berry et al 2019, Hull et al 2020. However, ours is the first to use camera traps to study the effects of both fine and larger-scale habitat characteristics and potential displacement by a conspecific on the occupancy of mule and white-tailed deer in an area of sympatry.…”
Section: Discussionmentioning
confidence: 99%
“…However, they overlap across a broad zone of sympatry, primarily along the Rocky Mountains and in the surrounding Plains regions (Geist 1998, Jacobson 2003, Lyman 2006, Hygnstrom et al 2008. Habitat use by free-ranging deer of both species has been extensively studied in areas of both allopatry and sympatry (see review in Berry et al 2019), primarily using an animal-based approach (i.e., observing groups of animals, following individual animals using radio telemetry, collecting fecal samples for microhistology, stable isotope analyses of liver tissue) (Anthony and Smith 1977, Lingle 2001, 2002, Walter et al 2009, Whitney et al 2011, Dellinger et al 2019. These studies and others demonstrated varying degrees of resource and habitat partitioning, generally finding that large-scale topographic variation or habitat association facilitates the segregation of these two species (Smith 1987, Woods et al 1989, Avey et al 2003, Whittaker and Lindzey 2004, Brunjes et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the early postfire years, burned areas may improve summer forage due to the increased light availability and nutrients that facilitate growth of forage biomass ( Mackie et al 2003 ;Greene et al 2012 ). The increased forage quality and quantity ( Schuyler et al 2021 ) can have a positive effect on individual fitness and survival ( Hobbs and Spowart 1984 ;Walter et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%